ARTIFICIAL INTELLIGENCE AND JOURNALISM PRACTICE IN NIGERIA: PERCEPTION OF JOURNALISTS IN BENIN CITY, EDO STATE - Guanah, Jammy Seigha; Agbanu, Venatus Nosike; Obi, Ijeoma (UI Scholars Hub, 2020)
The emergence of Artificial Intelligence (AI) is gradually having effects on every facet of the society; the mass media, being an indispensable part of any society, are not exempted from this AI bug hence they must synergise with new technologies to remain relevant. This study looked at how AI can, or has been impacting journalism practice in Benin City, Edo State, Nigeria. The study was anchored on the mediamorphosis theory while Survey and In-depth oral interview were adopted as the research methods for obtaining data. The 254 registered journalists under the Nigerian Union of Journalists (NUJ), Benin City Chapter, formed the population, and the sample size of 152 was determined using Cozby`s Precision of Estimate table. Among other findings, the study revealed the agreement of journalists in Benin City that automated journalism (usage of AI-driven media applications) is an improvement over the current reporting practices which are still done “manually.” It concluded that automation is the future, and Nigerian journalists cannot afford to be left out in the ultimate move to a world of automation, hence they have to prepare themselves, and embrace AI. Its recommendation included that Journalism schools should have curricula that embrace technology that will effectively prepare potential journalists for the future use of AI for their work.